Pendampingan Knowledge Sharing Penelitian Tindakan Kelas dalam Peningkatan Kompetensi Guru Pondok Pesantren Modern Saifullah An-Nadliyah - Junita, Audia; Wulandari, Novita; Rahayu, Yoni (Jurnal Penelitian dan Pengabdian Masyarakat, 2023)
This Community Service Activity (PKM) aims to disseminate useful knowledge regarding the usefulness of Classroom Action Research to improve the professional competence of teachers at the Saifullah An-Nadliyah Modern Islamic Boarding School. The PKM method takes the form of lectures, simulations and discussions. The results of activities measured using the oral question and answer method prove that there is an increase in the knowledge and understanding of participants (Islamic boarding school teachers) regarding the use of Classroom Action Research in Islamic boarding schools. The participants were motivated to apply the Classroom Action Research method in real terms in various aspects of the learning process. The realization of PKM activities is expected to increase quality learning output and outcomes, teacher professional competence, as well as the quality of Islamic boarding school institutions as a choice of place to study that is increasingly in demand by society today.